Remarks on maps of inverse limits - Kim, Dok Yong (Annales Mathematicae Silesianae, 1990)
The aim of this note is to give a short proof of the Ščepin theorem concerning maps of inverse limits. This theorem was generalized by several authors; see e.g. W. Kulpa [5], A. Archangelskii [1] and M.G. Tkačenko [7], [8]. Our method of the proof gives also the most general version of the Ščepin theorem due to Tkačenko. It can be also applied for obtaining in a very general setting the theorem of H.H. Corson and J.R. Isbell [3], [4] concerning maps from products.